In Vitro Immunomodulatory Effects of Selected Fruits and Herbs on Human Peripheral Blood Mononuclear Cells - Chai, Pei Shin (2010)
Although the immune system serves as the defensive mechanism of our body, a weakened or overactive immune system predisposes the body to infection and various other diseases such as cancers, allergies and immune diseases. Due to costs and the growing concerns regarding the side effects of conventional drugs, many patients are seeking alternative treatments. Natural food like fruits, herbs and spices has long been used in folklore remedies to cure many diseases and boost the immune system. In this study, the immunomodulatory effects of papaya (Carica papaya) fruits, mata kucing (Euphoria malaiensis) fruits, dang shen (Codonopsis pilosula) and Pu-erh tea (Camellia sinensis var. assamica)weredetermined using flow cytometry. A culture system using human peripheral blood mononuclear cells (PBMC) was used. High cell viability and increased proliferation of PBMC together with immunophenotyping results showed that the culture system provides a good system to study the subpopulations of PBMC. MTS and tritiated thymidine incorporation assay showed that these extracts have some proliferative effect on PBMC and limited cytotoxicity at the concentrations tested. Immunophenotyping results showed that papaya and mata kucing were able to upregulate the percentage of immune cells such as NK, NKT and monocytes (for papaya). They may also modulate regulatory functions, for example, by increasing Tregs and suppressing inhibitory cytokines such as IL10 (for papaya). Our results demonstrated that these fruits may have potential as immune-booster and regulator, anti allergy, anti cancer and anti inflammatory (papaya) agents. Dang shen and tea showed suppressive effect on proinflammatory cytokine production in cultured PBMC.We also observed stimulatory effect on the percentages of T cells (CD3+), B cells (CD3-19+), NK (CD3-56+), and NKT (CD3+56+) cells which could support their roles as traditional immune boosters. However, these food extracts were also observed to increase activation of immune cells (indicated by the expression of CD69+ and CD25+127+). Papaya and mata kucing also increased levels of certain proinflammatory cytokines. While these may be advantages during an infection however in the absence of one, activated cells may be detrimental to the body. Dang shen and teaalso showed suppressive effect on Tregs. Thus, we observed immunomodulatory effect of these extracts on immune cells in culture. These initial results should warrant further investigations into the immunomodulatory effects of papaya and mata kucing (immunostimulatory and immunoregulatory), dang shen and tea (immmunosuppression) on in vivo models to elucidate their potentials as food supplement to modulate the immune system.